An Approach to the Study of Laboratory Work From the Representations of Future Biology Teachers - Zorrilla, Erica (2021)
Introduction. This article presents a study conducted with 111 students of the Biology teacher training program in San Juan Province, Argentina, to know the students’ opinions, investigate their social representations related to the laboratory work, and analyze its impact on the current process and their future teaching performance. Method. The study was developed from a qualitative approach. The instrument implemented included a technique of evocation and hierarchical organization and a technique of incomplete phrases. Results. The results obtained show that the representations tend to focus on elements related to teaching, learning, and procedural aspects. At the same time, the opinions of the students indicate the scarce realization of experimental practices and the insufficient connection with the theoretical concepts studied. Conclusion. These results invite us to reflect on the need to increase and diversify experimental work in Biology teacher training to contribute to the future professional performance of these students at the secondary level.